Sonothrombolysis in Patients With Acute Ischemic Stroke With Large Vessel Occlusion: An Individual Patient Data Meta-Analysis. Issue 12 (25th August 2021) - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Eggers, Jürgen; Larrue, Vincent; Thomassen, Lars; Grotta, James C.; Seitidis, Georgios; Schellinger, Peter D.; Mavridis, Dimitris; Demchuk, Andrew; Novotny, Vojtech; Molina, Carlos A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Evidence about the utility of ultrasound-enhanced thrombolysis (sonothrombolysis) in patients with acute ischemic stroke (AIS) is conflicting. We aimed to evaluate the safety and efficacy of sonothrombolysis in patients with AIS with large vessel occlusion, by analyzing individual patient data of available randomized-controlled clinical trials. Methods: We included all available randomized-controlled clinical trials comparing sonothrombolysis with or without addition of microspheres (treatment group) to intravenous thrombolysis alone (control group) in patients with AIS with large vessel occlusion. The primary outcome measure was the rate of complete recanalization at 1 to 36 hours following intravenous thrombolysis initiation. We present crude odds ratios (ORs) and ORs adjusted for the predefined variables of age, sex, baseline stroke severity, systolic blood pressure, and onset-to-treatment time. Results: We included 7 randomized controlled clinical trials that enrolled 1102 patients with AIS. A total of 138 and 134 confirmed large vessel occlusion patients were randomized to treatment and control groups respectively. Patients randomized to sonothrombolysis had increased odds of complete recanalization compared with patients receiving intravenous thrombolysis alone (40.3% versus 22.4%; OR, 2.17 [95% CI, 1.03–4.54]; adjusted OR, 2.33 [95% CI, 1.02–5.34]). The likelihood of symptomatic intracranial hemorrhage was not significantly different between the 2 groups (7.3% versus 3.7%; OR, 2.03 [95% CI, 0.68–6.11]; adjusted OR, 2.55 [95% CI, 0.76–8.52]). No differences in the likelihood of asymptomatic intracranial hemorrhage, 3-month favorable functional and 3-month functional independence were documented. Conclusions: Sonothrombolysis was associated with a nearly 2-fold increase in the odds of complete recanalization compared with intravenous thrombolysis alone in patients with AIS with large vessel occlusions. Further study of the safety and efficacy of sonothrombolysis is warranted.